NILAI PENDIDIKAN KARAKTER DALAM NOVEL WARISAN CHAIRUL HARUN: SUATU KAJIAN DEKONSTRUKSI - DR. ZULFARDI. D , M.Pd (Menara Ilmu, 2016)
This studi aims discuss in depth the educational values of characters in Warisan novelfrom Chairul Harun work using the approach of deconstruction. This type of research isqualitative in the form of content analysis by using descriptive method. The data is analyzedusing the theory of semiotics, hermeneutics and literary reception. According to the finding,hermeneutic reading is done by using deconstruction study with the result as follows: thecharacter value is formed by indicator that beats selfhishnes to do sincerelly. Allah hatesdevorce. Religion is the fondation philosophy of minangkabau tradition, women dignity andleader dignity. The functions are education, affirmation of value and reflection of rural andurban community. The impacts inflictes are mindset change, the imaging about education,educated people, and new value ligitimation. The meaning formed is meaning back noble valuethat has been manipalated to individual and group interests, human dialectics and the culture.Keywords : value character education , deconstruction, novel